Cowpea mottle virus: field resistance and seed transmission in virus tolerant cowpea - Allen, D.J.; Thottappilly, G.; Rossel, H.W. (1982)
Cultivars of cowpea (Vigna unguiculata) possessing tolerance to infection by cowpea mottle virus (CMeV) under screenhouse conditions exhibited both tolerance and resistance to infection by beetle vectors under field conditions. Resistance to infection was exemplified by delayed and reduced incidence of infection resulting from natural infection pressure, and appeared to be unrelated to vector feeding preference. This suggests that certain cowpea cultivars such as TVu 3901 possess more than one component of resistance (sensu Russell, 1978) to CMeV. Despite some correspondence between results from artificial (mechanical) and natural (vector) inoculation, we suggest that field evaluation is often an important adjunct to greenhouse screening for virus disease resistance since resistance mechanisms operative under field conditions may be overlooked in artificial screening programmes. In the susceptible cultivar TVu 612, when artificially inoculated, CMeV is transmissible through cowpea seed up to 0.4%. In only one instance was CMeV seed transmitted from natural infection. We suggest that apparent inefficiency in seed transmission may in part account for the restricted ecological and geographical distribution of CMeV.